The Mite Tyrophagus putrescentiae Hosts Population-Specific Microbiomes That Respond Weakly to Starvation - Nesvorná, Marta; Bittner, Václav; Hubert, Jan (Microbial ecology, 2019)
The effect of short-term nutrient deprivation was studied in five populations of the mite Tyrophagus putrescentiae with different microbiomes. The fresh weight, nutrient status, respiration, and population growth of the mites were observed for the five mite population-scale samples. The starvation caused the larvae and nymphs to be eliminated, resulting in a significant increase in the fresh weight of starved adult specimens. Three populations were negatively influenced by starvation, and the starved specimens were characterized by a decrease in nutrient status, respiration, and population growth. One population was not influenced or was slightly influenced by starvation, which had no effect on population growth or nutrient contents but caused a significant decrease in respiration. One population was positively influenced by starvation; the population growth increased in starved specimens, and starvation had no effect on respiration. Although starvation altered the bacterial profiles of the microbiomes, these differences were much smaller than those between the populations. The bacterial profiles of Staphylococcus, Bacillus, Kocuria, Brevibacterium, and unidentified Micrococcaceae and Enterobacteriaceae increased in starved specimens, whereas those of Bartonella and Solitalea-like genera were reduced in the starved mite populations. The profiles of the intracellular symbiont Cardinium decreased in the starved specimens, and the Wolbachia profile changes were dependent on the mite population. In mite populations, when the symbionts were rare, their profiles varied stochastically. Correlations between changes in the profiles of the bacterial taxa and mite fitness parameters, including nutrient status (lipids, proteins, saccharides, and glycogen contents), mite population growth, and respiration, were observed. Although the microbiomes were resistant to the perturbations caused by nutrition deficiency, the responses of the mites differed in terms of their population growth, respiration, and nutrient status.
Keywords: Animals; stravovací zvyklosti; Host Specificity; hostitelská specificita; Bacterial Physiological Phenomena; mikrobiota; zvířata; fyziologie bakterií; Acaridae; Feeding Behavior; Bacteria; Microbiota